A Direct Cortico-Nigral Pathway as Revealed by Constrained Spherical Deconvolution Tractography in Humans - Cacciola, Alberto; Milardi, Demetrio; Anastasi, Giuseppe P.; Basile, Gianpaolo A.; Ciolli, Pietro; Irrera, Mariangela; Cutroneo, Giuseppina; Bruschetta, Daniele; Rizzo, Giuseppina; Mondello, Stefania; Bramanti, Placido; Quartarone, Angelo (Frontiers in Human Neuroscience, 2016)
Substantia nigra is an important neuronal structure, located in the ventral midbrain, that exerts a regulatory function within the basal ganglia circuitry through the nigro-striatal pathway. Although its subcortical connections are relatively well known in human brain, very little is known about its cortical connections. The existence of a direct cortico-nigral pathway has been demonstrated in rodents and primates but only hypothesized in humans. In this study, we aimed at evaluating cortical connections of substantia nigra in vivo in human brain, by using probabilistic constrained spherical deconvolution tractography on magnetic resonance diffusion weighted imaging data. We found that substantia nigra is connected with cerebral cortex as a whole, with the most representative connections involving prefrontal cortex, precentral and postcentral gyri and superior parietal lobule. These results may be relevant for the comprehension of the pathophysiology of several neurological disorders involving substantia nigra, such as parkinson’s disease, schizophrenia and pathological addictions.